Low-grade fibromyxoid sarcoma: a rare condition with high proliferation - Karimi Khezri, Marzieh; Taşkapılıoğlu, M. Özgür; Türkkan, Alper; Yalçınkaya, Ulviye; Bekar, Ahmet (The European Research Journal, 2018)
Low-grade fibromyxoid sarcoma (LGFMS) is a type of high metastatic potential of the fibrosarcomas. Most of the time there is a long interval between tumor presentation and metastasis. We present 2 cases of LGFMS. The first is a 31-year-old female with a mass in anterior aspect of her left thigh, and the other is a 68-year-old female with mass in posterior of her neck. Both cases underwent operation for several times and confirmed as LGFMS histopathologically, there is no exact protocol for postoperative follow-up to detect early metastases according to the relative variety of LGFMS. So informing the patients about the long-standing metastatic potential of their disease is important.